MEDIA REPRESENTATION OF MULTICULTURALISM EDUCATION - Muhammad Hifdil Islam (At- Ta'lim : Jurnal Pendidikan, 2024)
This research is to investigate how mass media portray multiculturalism education in the modern world. Multiculturalism in the modern world. The research investigated how the media shows the diversity of cultures, values, and identities in society through a qualitative content analysis of popular television programs, news articles, and news articles. Through qualitative content analysis of popular television programs, news articles, and online publications. This method provides an understanding of how the media influences people's perceptions of multiculturalism and how these representations can influence social constructions relating to justice, identity, and inclusion. We found that our results provided us with a better understanding of how the media plays an important role in changing the way people think about an important role in changing the way people think about multiculturalism and its socialization in modern society.